Influencia de la motivación en el rendimiento laboral de los colaboradores de la empresa contratista minera Canchaya Ingenieros S.R.L. consorcio minero horizonte S.A. distrito de Parcoy - provincia de Pataz: 2016. - Ruíz Felix, Mary Esther (2016)
This thesis was performed with the purpose to explain the influence of the motivation in the work performance of the collaborators of the Mining Company Contractor Canchanya Ingenieros S.R.L. Consorcio Minero Horizonte, district of Parcoy- province Pataz, in the period 2016. It has been considered to be the kind of applied research, taking as a basis a explanatory design, and the sample consisted of 207 collaborators, with whom we worked by applying the methods and techniques of quantitative and qualitative investigation. The results obtained can be inferred that the poor conditions food and accommodation in the mining camp, in addition to the lack incentives, labor surveys, poor interpersonal relationships between colleagues and with their heads immediate superiors, become the principal factors that generate demotivation and consequently affect the performance working in this mining company. Finally, we consider that the Company through the Department of Human Resources should implement a motivational program that promotes public recognition of employees, incentives for compliance task, the quality of interpersonal relationships between co-workers and good treatment by bosses area, staff training and maintain close communication with the partner, repowering working conditions. On the other hand promote organizational leadership and teamwork; to improve work performance; which will be reflected in the level of production and productivity of the company.